Implementation of E-Module Based on Problem-Based Learning to Decrease Misconception and Increase Problem Solving Skill in the Topic Of Ecology For Grade X-1 SMA N 1 Ngemplak Boyolali Academic Years 2014/2015 - Afifah Putri Sari; Puguh Karyanto; Yudi Rinanto (Universitas Sebelas Maret, 2015)
The purpose of this research is to decrease misconception and increase problem solving skill of the students in the X-1 SMA N 1 Ngemplak Boyolali academic years 2014/2015 by using e-module based on Problem-Based Learning. The subject of research is the students in X-1 of SMA N Ngemplak Boyolali academic years 2014/2015. Research method is class action reseach which consists of two cycles. This research used qualitative descriptive study. Data validation used triangulation of methods that consists of observation, interview, and documentation. The instrument to measure problem solving skill and misconception used test. The target of descent misconception is 20% and improvement problem solving skill is 70% in the end of cycle. Result of this research in the end of cycle shows that there is a descent of misconceptions that is 19,61% in concept of population, 19,85% in concept of comunity, 20,59% in concept of ecosystem, and 26,47% in concept of ecology in science, enviroment, technology, and comunity (salingtemas). Salingtemas include science phenomenon in ecosystem enviroment and related to technology application and impact for society. The percentage of the problem solving’s aspects increased 72,43% in exploring and understanding, 73,16% in representing and formulating, 70,22% in planning and executing, and 70,22% in monitoring and reflecting. The conclusion of this research is the implementation of e-module based on Problem-Based Learning can decrease the students’s misconception and increase problem solving skill in the X-1 SMA N 1 Ngemplak Boyolali academic years 2014/2015.Keywords: E-module based on Problem-Based Learning, problem solving skill, misconception.